The Seed Semipermeable Layer and Its Relation to Seed Quality Assessment in Four Grass Species - Lv, Yan Y.; He, Xue Q.; Hu, Xiao W.; Wang, Yan R. (Frontiers in Plant Science, 2017)
The existence of a semipermeable layer in grass seeds has been extensively reported, yet knowledge of its influence on tests for seed viability and vigor that depend upon measurement of electrical conductivity (EC) is limited. This study determined the presence and location of the semipermeable layer, and its relation to seed viability and vigor assessment, in seeds of four important grass speciesElymus nutans Griseb., Lolium perenne L., Leymus chinensis (Trin.) Tzvel., and Avena sativa L. Intact seeds of E. nutans, Lolium perenne, and Leymus chinensis exhibited little staining with triphenyl tetrazolium chloride (TTC), and there were no differences in EC between seeds with different germination percentage (GP) (P > 0.05). After piercing the seed coat, however, all three species displayed positive staining with TTC, along with a significant negative correlation between EC and GP (E. nutans: R2 = 0.7708; Lolium perenne: R2 = 0.8414; Leymus chinensis: R2 = 0.859; P < 0.01). In contrast, both intact and pierced seeds of A. sativa possessed a permeable seed coat that showed positive staining with TTC and EC values that were significantly negatively correlated with GP (R2 = 0.9071 (intact) and 0.9597 (pierced); P < 0.01). In commercial seed lots of A. sativa, a field emergence test indicated that EC showed a significant negative correlation with field emergence at two sowing dates (R2 = 0.6069, P < 0.01 and 0.5316, P < 0.05). Analysis of seed coat permeability revealed the presence of a semipermeable layer located in the seed coat adjacent to the endosperm in E. nutans, Lolium perenne, and Leymus chinensis; however, no semipermeable layer was observed in A. sativa. This is the first report of the absence of a semipermeable layer in a grass species. The existence of a semipermeable layer is one of the most important factors affecting seed viability and vigor testing (based on EC measurement) in E. nutans, Lolium perenne, and Leymus chinensis. Increasing the permeability of the semipermeable layer, e.g., by piercing the seed coat, may permit the use of EC measurement to assess seed vigor in species that possess such a layer.